Association between Vascular Endothelial Growth Factor (VEGF) -1154G/A Polymorphism and Endometriosis in North West of Iran - Niaei, Gholamreza; Heidaryan, Somayeh; Niaei, Alireza; Alsadat Didevar, Nasim (Archives of Advances in Biosciences, 2017)
Endometriosis is considered as a multifactorial disease that affects up to 10% of all women of fertile age. Vascular endothelial growth factor (VEGF) is one of the most important activators of angiogenesis. VEGF is known to be a key molecule in the pathogenesis of endometriosis. A great number of studies have referred to genetic polymorphisms as a factor that contributes to the development of endometriosis. The present study was aimed to find out the frequency of the VEGF -1154G/A polymorphism and its relationship with endometriosis risk in Iranian women with endometriosis.This study involved 175 patients with endometriosis and 131 healthy controls. Following extraction of genomic DNA from patients and controls, genotyping of the -1154G/A polymorphism of the VEGF gene were performed by polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) analysis. Multivariate analysis was used to examine the association between the risk of endometriosis and VEGF -1154G/A polymorphism. There was statistically a significant difference in the frequency of the -1154G/A polymorphism between patients and the controls. The percentage distribution of the three -1154G/A genotypes was (GG 3.4%, GA %46.8%, AA 49.7%) in endometriosis patients. Conclusion: Data supports the hypothesis that angiogenesis is of pivotal importance in the development of endometriosis. Our study indicates that there is significant association between the VEGF gene -1154G/A polymorphism and the risk of endometriosis in North West of Iran.